PENGEMBANGAN ALAT PERAGA SIKLUS MAKHLUK HIDUP PADA PEMBELAJARAN IPAS KELAS III SEKOLAH DASAR - Batubara, Suci Ramadhani; Muchtar, Zainuddin (Universitas Negeri Medan, 2025)
The purpose of this study was to design and evaluate the feasibility, usability, and effectiveness of the SIKMAHI (Life Cycle of Living Things) learning media as a tool for teaching IPAS to third-grade elementary school students. The background of this study stems from the low level of students’ interest and learning outcomes related to the topic of life cycles, which is caused by monotonous teaching methods and the limited use of concrete learning media. This research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects consisted of 18 third-grade students at SDN 060857 Durung. Data were collected through observation, interviews, documentation, questionnaires, and tests (pretest and posttest). Validation results from subject matter experts, media experts, and teachers indicated that the SIKMAHI media is highly feasible for use. Usability testing showed that teachers found the media easy and engaging to apply in the learning process. Furthermore, the pretest and posttest results demonstrated a significant improvement in students’ learning outcomes. In conclusion, the SIKMAHI learning media is effective for use in IPAS learning, particularly for the topic of life cycles of living things. This media is able to enhance students’ understanding, increase learning interest, and encourage active participation in the teaching and learning process.